Pulmonary effects of expiratory‐assisted small‐lumen ventilation during upper airway obstruction in pigs1. (16th July 2015) - Ziebart, A.; Garcia‐Bardon, A.; Kamuf, J.; Thomas, R.; Liu, T.; Schad, A.; Duenges, B.; David, M.; Hartmann, E. K.
Summary: Novel devices for small‐lumen ventilation may enable effective inspiration and expiratory ventilation assistance despite airway obstruction. In this study, we investigated a porcine model of complete upper airway obstruction. After ethical approval, we randomly assigned 13 anaesthetised pigs either to small‐lumen ventilation following airway obstruction (n = 8) for 30 min, or to volume‐controlled ventilation (sham setting, n = 5). Small‐lumen ventilation enabled adequate gas exchange over 30 min. One animal died as a result of a tension pneumothorax in this setting. Redistribution of ventilation from dorsal to central compartments and significant impairment of the distribution of ventilation/perfusion occurred. Histopathology demonstrated considerable lung injury, predominantly through differences in the dorsal dependent lung regions. Small‐lumen ventilation maintained adequate gas exchange in a porcine airway obstruction model. The use of this technique for 30 min by inexperienced clinicians was associated with considerable end‐expiratory collapse leading to lung injury, and may also carry the risk of severe injury.